STUDY ON STRATEGIES FOR TRAINING OF A HANDBALL TEAM TO THE JUNIORS II (GYMNASIUM, 2009)
We have chosen this theme, being convinced that the subject of the paper work has an updatedcontent and based on a careful analysis could be applied even in practical activity might help those who aredirectly involved in this sport, as coaches and players.This point of view is regarding the determination of the training strategies of Junior II teams, so thatthey could contribute to the knowing of the level of the handball game at the moment.Results of content analysis, allow us to highlight the high level of flexibility and adaptability ofcomplex algoritmizate means targeting a comprehensive approach to ensure the educational training processat all stages of sports training.Using specific means of achieving the objectives, determined to improve indices tested at this levelof performance the team CSS. Bacau.